The European Commission’s half-finished digitalization strategy: a critical assessment by UNI Europa (Brussels, 2015)
"The digital future is already here - the digitalisation of Europe is exciting but carries with it challenges as well as opportunities. Europe needs to respond quickly to this development to ensure that it leads to economic growth, quality jobs, a skilled workforce and social justice.The European Commission has responded to digital development with the Digital Single Market Package (the DSM Package) and with it hopes to ensure the proper functioning of the single market by facilitating digitalisation and addressing challenges like geo-blocking, EU copyright and telecom rules, and high costs of parcel delivery in Europe.Although UNI Europa welcomes the Commission’s effort to respond to digital development, it finds the Commission’s approach too narrow and consumer-focused and lacking in emphasis on how this development affects workers, industries and services.